2017
DOI: 10.1038/jhh.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of interleukin-6 (IL-6) gene increases the risk of essential hypertension: a matched case–control study

Abstract: Essential hypertension (EH) is a chronic disease with clear epigenetic component. Inflammation and endothelial dysfunction have a great role in the development of persistent blood pressure elevation. The aim of this study was to explore an association between EH and DNA methylation in pro-inflammation cytokine gene interleukin-6 (IL-6) during the inflammatory process. We performed methylation analysis of peripheral blood DNA using bisulphite pyrosequencing technology between 96 EH patients and 96 age- and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
1
20
0
2
Order By: Relevance
“…Increasing the methylation level of a promoter region will silence the transcription of the corresponding gene, whereas decreasing it may promote gene transcription . Aberrant gene methylation has been identified as an important contributor to the pathogenesis of EH, for example, hypomethylation of interleukin‐6 ( IL‐6 ), angiotensin II type 1 receptor ( AGTR1 ), angiotensin‐converting enzyme ( ACE ), Na+/K+/Cl− cotransporter protein 1 ( NKCC1 ), and α‐adducin ( ADD1 ), and the hypermethylation of 11β‐hydroxysteroid dehydrogenase type II ( 11β‐HSD‐2 ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the methylation level of a promoter region will silence the transcription of the corresponding gene, whereas decreasing it may promote gene transcription . Aberrant gene methylation has been identified as an important contributor to the pathogenesis of EH, for example, hypomethylation of interleukin‐6 ( IL‐6 ), angiotensin II type 1 receptor ( AGTR1 ), angiotensin‐converting enzyme ( ACE ), Na+/K+/Cl− cotransporter protein 1 ( NKCC1 ), and α‐adducin ( ADD1 ), and the hypermethylation of 11β‐hydroxysteroid dehydrogenase type II ( 11β‐HSD‐2 ) …”
Section: Introductionmentioning
confidence: 99%
“…important contributor to the pathogenesis of EH, for example, hypomethylation of interleukin-6 (IL-6), 6 angiotensin II type 1 receptor (AGTR1), 7 angiotensin-converting enzyme (ACE), 8 Na+/K+/Cl− cotransporter protein 1 (NKCC1), 9 and α-adducin (ADD1), 10 and the hypermethylation of 11β-hydroxysteroid dehydrogenase type II (11β-HSD-2). 11 Serine hydroxymethyltransferase 1 (SHMT1), located on chromosome 17p11.2, is a key enzyme involved in folic acid metabolism.…”
mentioning
confidence: 99%
“…Accumulating evidence indicates that IFN-γ, the first cytokine identified in endothelial cells, induces the expression of major histocompatibility complex genes and enhances the antiviral activity of immune cells (Lubina-Dąbrowska et al 2017). Furthermore, some studies revealed that the methylation of proinflammatory-cytokine genes is associated with blood pressure, e.g., genes of C-reactive protein, IL-6, IL-1 beta (IL-1β), and tumor necrosis factor α (Sullivan et al 2007;Lópezjaramillo et al 2008;Bay-Richter et al 2012;Mao et al 2017b). However, the methylation status of IFNG among EH patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that hypomethylation mechanisms can lead to higher ACE, β‐adrenergic receptors and Na + channel expression in the hypertensive condition . In agreement with this, it was recently demonstrated that the hypo‐methylation process of the angiotensin II type I receptor (AGTR1) and interleukin‐6 gene in peripheral blood DNA, increase the risk of essential hypertension in human.…”
Section: Epigenetic Modifications: a Potential Pathway Linking Maternmentioning
confidence: 59%